Decision Support System for Determining the Village Secretary Using the Analytic Hierarchy Process Method in the Village of Kubah Sentang Pantai Labu - Petti Sijabat (Jurnal ICT : Information and Communication Technologies, 2022)
The election of the village secretary is an election chosen by the village head himself and is not carried out in a democratic manner. So far, what the village government has done in the election of the village secretary has not been effective. This system was built using the Analytic Hierarchy Process (AHP) method, which is one of the methods used in decision support systems. The AHP method is by weighting each criterion and sub-criteria. The results of the study were in the form of a decision support system application for determining village secretaries using Visual Studio 2010 so as to be able to select several candidates for village secretaries who were worthy of the position as village secretary.